Russian political and economic interests in Libya (Journal of Human Sciences, 2025)
This research paper, titled "Russian Political and Economic Interests in Libya," describes and analyzes the most important interests that Russia is working to achieve. The first section addresses political and security interests, while the second section focuses on economic and commercial interests. The research paper concludes with a key finding: Russia's interests in Libya are of similar importance, with each interest working to support the other within the state's sphere of interests.